Associations between pregnancy loss and common mental disorders in women: a large prospective cohort study - Shen, Qiaoqiao; Zhong, Wenfang; Wang, Xiaomeng; Fu, Qi; Mao, Chen (Frontiers in Psychiatry, 2024)
Background: Increasing evidence suggests that pregnancy loss can lead to negative emotional outcomes, such as anxiety and depression, for women. However, limited knowledge exists regarding the long-term risk of mental disorders among individuals who have experienced pregnancy loss.Objective: To investigate the associations between pregnancy loss and the risk of common mental disorders.Methods: In the UK Biobank, a total of 218,990 women without any mental disorder at baseline were enrolled between 2006 and 2010 and followed until October 2022.Information on the history of pregnancy loss was obtained through self-reported questionnaires at baseline. Cox proportional hazard regression models were used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between pregnancy loss and common mental disorders.Results: During a median follow-up time of 13.36 years, there were 26,930 incident cases of common mental disorders. Incidence rates of common mental disorders were elevated among women with a history of stillbirth (HR 1.15, 95% CI: 1.07-1.23), miscarriage (HR 1.06, 95% CI: 1.02-1.10), or pregnancy termination (HR 1.21, 95% CI: 1.17-1.25) compared to those without such experiences. Furthermore, the risk of common mental disorders significantly increased in women with two or more miscarriages (HR 1.14, 95% CI: 1.08-1.19) or two or more pregnancy terminations (HR 1.39, 95% CI: 1.30-1.48).Conclusions: Pregnancy loss is associated with an increased risk of common mental 3 disorders in women later in life. These findings may contribute to the enhancement of long-term monitoring and prevention of common mental disorders for women with such a history.